Interaction Pattern Between Trainees and Employees at InterContinental Bali Resort - Perwira, Novandi Indra; Ariana, Nyoman; Rahyuda, Irma (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 3 (2018): Vol.2,No.3,2018DO - 10.24843/JKH.2018.v02.i03.p01, 2019)
Internship is an essential program to implement by educational institutions since through internship students can have direct experience in the working world. Acceptance of trainee in the tourism industry is necessary because it could help to increase work force as well as to select candidates to employ as new workers. However, in practice, internship program faces some obstacles, and one of them is the interaction process between the interns and existing workers. Considering this problem, this study will discuss patterns of interaction between trainees and employees at the InterConntinental Bali Resort. Data were collected through questionnaire, interview, observation, and literature review. The sampling technique follows Slovin’s quota based formula, while base informants and key informants were determined through purposive random sampling technique. Questionaire was analyzed with statistical and qualitative descriptive methods. The interaction pattern in the InterContinental Bali Resort could be classified into two categories, namely associative and dissociative. The associative pattern includes cooperation, accommodation, adaptation and assimilation, while dissociative involves competition, contravention and conflict. The dominant pattern in the InterContinental Bali Resort is the associative pattern of interaction, with its three sub indicators, namely cooperation, accommodation or adaptation and assimilation, are categorized as fine. Meanwhile, two out three sub indicators of dissociative interaction, that is contravention and conflict, could be categorized as minor and quite insignificant. However, the first sub indicator of dissociative interaction, namely competition, is categorized as medium. As such, this study would like to advice the InterContinental Bali Resort to pay more attention to the dissociative pattern of interaction, especially Competition, in order that service in InterContinental Bali Resort can be enhanced.